Ulcerative colitis combined with isolated superficially serrated adenoma: a Case Report - Hua Gao; Jinshan Nie; Lipin Zhang; Chen Gong (Frontiers in Oncology)
IntroductionSuperficially serrated adenoma (SuSA) is a recently identified type of serrated lesion characterized by a combination of adenomatous and serrated features. There are limited reports on SuSA currently, and its occurrence in conjunction with ulcerative colitis (UC) has not yet been documented.Case presentationWe present the case of a 38-year-old male with a 13-year history of ulcerative colitis (UC). During a routine follow-up colonoscopy, a superficial elevated lesion with a whitish surface was detected in the rectum, 10 cm from the anal verge. The lesion was removed en bloc via endoscopic submucosal dissection (ESD). Pathological analysis showed a combination of superficial serrated and vertically oriented adenomatoid glands. Immunohistochemistry indicated that the superficial epithelial cells exhibited serrated features and expressed CK20, while the middle and lower mucosal layers tested positive for Ki-67.ConclusionAlthough some studies have explored SuSA, many aspects of the disease remain unclear. This is the first reported case of UC combined with SuSA. Future reports are essential to enhance understanding of the potential link between UC and SuSA.